Adopting trust and assurance as indicators for the reassignment of responsibilities in multi-agent systems. (25th March 2015) - Gâteau, Benjamin; Ouedraogo, Moussa; Feltus, Christophe; Guemkam, Guy; Danoy, Grégoire; Seredynski, Marcin; Khan, Samee U.; Khadraoui, Djamel; Bouvry, Pascal
Abstract: Multi-agent systems have been widely used in the literature, including for the monitoring of distributed systems. However, one of the unresolved issues in this technology remains in the reassignment of the responsibilities of monitoring agents when some of them become unable to meet their obligations. This paper proposes a new approach for solving this problem based on (a) the gathering of evidence on whether the agent can or cannot fulfil the tasks it has been assigned and (b) the reassignment of the task to alternative agents using their trust level as a selection parameter. A weather station case study is proposed as an instantiation of the proposed model.